KARAKTER SUTAWIJAYA DALAM TARI PENANGSANG SUTAWIJAYA - Hendrawan, Mochamad; Hartanto, Hartanto (Greget : Jurnal Kreativitas dan Studi Tari, 2023)
The research entitled "Karakter Sutawijaya dalam Tari Penangsang Sutawijaya" focuseson the discussion of the character of the Sutawijaya figure. Sutowijoyo’s character is interpreted as a smooth, dexterous, skillful and sigrak. The work carried out find this character with an emphasis on the elements of movement and the application of Javanese dance musical concepts. This research is intended to describe the character, the creative process of dancing, and the form of dance presentation.The research used is qualitative research by looking at object empirically. Data collectin through observation, interview, and literature studies. Observation emphasizes on the quality of Surakarta style dance performance, interviews and literature studies as a complement to observation and to support knowledge about characterization. Description of Sutawijaya's character through book references, interpretations of dance creators, and interpretations of dancers. The creative process of dancing, using Srihadi's theory. The discussion of the form of dance presentation uses Maryono's theory. The results of this study are in the form of a dance presentation that reveals about Sutawijaya by having an authoritative character, andap asor, firm, and doubtful. The creative process is manifested in the development of scene patterns, motion, clothing, and music. The form of offering the Penangsang Sutawijaya dance is a paired dance with the theme of war. This dance is presented by two male dancers, the dashing son and the alus madya son.